Pembelajaran PAI berbasis integratif inklusif untuk menumbuhkan sikap moderasi beragama - Tri Hidayatul Septiana; Muhammad Misbah (Sekolah Tinggi Agama Islam (STAI) AL-IKHLAS DAIRI SIDIKALANG, 2026)
The expansion of digital technology and globalization has transformed the ways in which young people access, interpret, and practice religious teachings. Although the availability of digital religious resources broadens learning opportunities, it also creates challenges associated with intolerance, ideological polarization, and the circulation of extremist religious narratives. In this context, strengthening religious moderation through education has become increasingly important, particularly within Islamic Religious Education (IRE). This study investigates the contribution of an integrative-inclusive learning approach in IRE to the development of students’ religious moderation. Using a qualitative library research design, the study examines relevant scholarly literature, including academic books, journal articles, and policy documents. Data were analyzed through data reduction, categorization, interpretation, and conclusion drawing. The findings demonstrate that integrative-inclusive IRE learning supports the cultivation of core values of religious moderation, including tolerance, justice, balance, openness, and respect for diversity. The approach also facilitates the development of critical thinking, digital literacy, and social awareness, enabling students to engage constructively with the complexities of multicultural societies. Furthermore, contextual, dialogical, and humanistic learning practices encourage students to move beyond normative understandings of Islam toward the practical application of moderation values in everyday life. The study concludes that integrative-inclusive IRE provides a relevant pedagogical framework for promoting religious moderation and preparing students to participate responsibly in pluralistic social environments.